ILO Convention no. 189: Notes on the ratification process in Brazil - Monticelli, Thays; Fraga, Alexandre Barbosa (Estudos Avançados, 2023)
The article aims to analyze the ratification process in Brazil of the Convention on Decent Work for Domestic Workers (n.189). The method is based on document analysis and interviews with members of Fenatrad (National Federation of Domestic Workers). There is a contradiction between the process of defining and approving of C189 and the path followed later for its ratification, especially in the dialogue between actors and partners historically involved in the struggle for the rights for this professional category. The article thus seeks to contribute to the analysis of the relationships between social movements and the State.